Improvement of the Procedure for Sanitary and Quarantine Control of Ships in the Seaports - Yu. V. Ryzhkov; N. D. Pakskina; E. A. Moskvitina (Проблемы особо опасных инфекций, 2018)
Objective of the work is to analyze the procedure of ship sanitary and quarantine control in the Rostov Region seaports in order to identify the risks for sanitary and epidemiological welfare of the population and to improve communication process between the authorized ports. Materials and methods. Ship sanitary and quarantine control data on 8314 ships that arrived at Rostov-on-Don, Azov and Taganrog sea border checkpoints were used, considering possible risks for the sanitary and epidemiological welfare of the population. Results and conclusions. The key risks for decision-making whether to perform ship sanitary and quarantine control at the sea border checkpoints are identified. At the stage of the implementation of IHR (2005) it is necessary to consider the ship sanitary and quarantine control at the sea border checkpoints as an unscheduled inspection; availability of preliminary information on the absence of valid sanitary certificates on ships arriving from abroad to be the ground for carrying out ship sanitary and quarantine control at the sea border checkpoints. In order to improve the communication process between authorized ports it is necessary to insert the results of the inspections into ship’s sanitary certificates with issuance of the revealed risks forms.